1996
DOI: 10.1182/blood.v87.4.1368.bloodjournal8741368
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal inside-out signal transduction-dependent activation of glycoprotein IIb-IIIa in a patient with impaired pleckstrin phosphorylation

Abstract: Platelet-agonist interaction results in activation of glycoprotein (GP) IIb-IIIa complex and fibrinogen binding, a prerequisite for platelet aggregation. Fibrinogen binding exposes new antibody binding sites on GPIIb-IIIa (ligand-induced binding sites: LIBS). Signal transduction events, including pleckstrin phosphorylation by protein kinase C (PKC), are considered to regulate GPIIb-IIIa activation. We studied a 16-year- old white male with lifelong mucocutaneous bleeding manifestations and abnormal platelet ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
40
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 32 publications
4
40
1
Order By: Relevance
“…The right panel shows the increase in the radioactivity in free arachidonic acid, reflecting the release of free arachidonic acid upon platelet activation aggregation responses were markedly diminished in response to multiple agonists. 6 This provides a mechanism for the markedly decreased aggregation responses. Impaired thromboxane production compromises responses to platelet agonists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The right panel shows the increase in the radioactivity in free arachidonic acid, reflecting the release of free arachidonic acid upon platelet activation aggregation responses were markedly diminished in response to multiple agonists. 6 This provides a mechanism for the markedly decreased aggregation responses. Impaired thromboxane production compromises responses to platelet agonists.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] In addition, abnormalities in mechanisms that regulate secretion have been reported in some patients, 2,3,5 including in myosin light chain and pleckstrin phosphorylation, and decreased platelet PKCθ. 6,7 Platelet mRNA expression profiling of a patient with RUNX1 mutation 8 and other studies 7 have shown downregulation of several genes, including MYL9, PRKQ ALOX12 and PF4, and some of these are direct transcriptional targets of RUNX1, providing evidence for aberrations in multiple platelets mechanisms, including in those regulating platelet responses to activation. 2,[9][10][11][12] Platelets possess three distinct types of granules-dense and α-granules, and acid hydrolase (AH)-bearing vesicles (lysosomes), whose contents are secreted on platelet activation.…”
Section: Introductionmentioning
confidence: 88%
“…These include abnormalities in the integrin per se , resulting in impaired ligand binding or its activation and in the upstream signalling events that regulate GPIIb–IIIa function, unrelated to any abnormality in the integrin. Evidence for the latter type of signalling‐related abnormality in GPIIb–IIIa activation has been shown in some patients (Gabbeta et al , 1996; 1997).…”
mentioning
confidence: 99%
“…LIBS expression on receptor activation is a signal transduction‐dependent process; however, under certain conditions (e.g. exposure to small RGD‐containing compounds), it can be induced in a signal transduction‐independent manner (Du et al , 1991; Gabbeta et al , 1996).…”
mentioning
confidence: 99%
See 1 more Smart Citation